In vitro cell proliferation assay for measuring the cytotoxic effects of spironolactone (SPIR) in osteosarcoma cell line / Farhana Khamarudin ... [et al.] - Khamarudin, Farhana; Muhamad, Mudiana; Ibrahim, Mohammad Johari; Wan Mohamad Zain, Wan Nor I'zzah; Ab-Rahim, Sharaniza (Universiti Teknologi MARA, Pulau Pinang, 2022)
Cancer cell lines are used to study malignancies, cell biology, and drug discovery. For this reason, osteosarcoma (OS) cell lines have the potential to be useful models for the investigation of osteosarcoma progression and treatment. Osteosarcoma is a primary malignant bone tumour affecting mostly children and adolescents. Spironolactone (SPIR), is an FDA-approved diuretic drug with a long-term safety profile used to treat hypertension and kidney disease. Previous research has found that SPIR also is able to up-regulate Natural Killer Group Member D (NKG2D) Ligand in multiple cancer cell lines by activating the ATM-Chk2-mediated checkpoint pathway, which in turn enhances tumour elimination by natural killer cells, supporting a role in cancer immune response. In addition, NKG2D is an activating receptor that can bind to a wide range of stress-induced ligands found in cancer or viral infection. Therefore, the purpose of this study is to determine the effect of SPIR on cell viability of highly metastatic osteosarcoma (HOS-143B) cells and human foetal osteoblast (hFOB) cells. SPIR was treated to HOS-143B cells at doses ranging from 5 to 40μM with human foetal osteoblast, hFOB as controls. Cytotoxicity level of SPIR was determined at post- 24, 48 and 72 hours using the cell proliferation assay. At post-24 and 48 hours, the SPIR exhibited an effect on HOS-143B as evidenced by the consistent pattern of high percentages (80% and greater) of viable cells at all doses. Meanwhile, during the incubation period, SPIR had a dose-dependent impact on hFOB cells, with viable cell percentages ranging from 95% to 35%. Taken together, these findings indicate that when SPIR was given at doses below its cytotoxic limit, it had an overall beneficial effect on the proliferation of OS cancer cells.